Public Speaking dan MC : Meningkatkan Kemampuan Berbicara dan Memimpin Acara di Karang Taruna Sagan RW 07: Public Speaking dan MC : Meningkatkan Kemampuan Berbicara dan Memimpin Acara di Karang Taruna Sagan RW 07 - Fahrizal, Ari; Rismawati; Indri Novyana; Rafi Mahardika; Desiree Sahabuddin; Andiyansari, Popi (Jurnal ABDI RAKYAT, 2024)
In the current era of communication which has developed rapidly, having public speaking skills is a crucial factor that greatly influences the success of an individual in conveying his or her ideas. This development also encourages an increase in the need for public speaking skills and leading events. However, until now many individuals still have difficulty, especially the younger generation, in conveying messages well and confidently, especially when the message is conveyed in public. Therefore, public speaking and MC (Master of Ceremony) training for Karang Taruna youth in Sagan Hamlet RW 07, Terban, Gondokusuman, D.I. Yogyakarta, because after observation and dialogue with the Karang Taruna Dusun Sagan, RW 07, it was found that they also experienced difficulties in conveying messages in public.